COMPARISON OF THE EFFECT OF INTRA-CUFF KETAMINE VERSUS ALKALINIZED LIDOCAINE FOR PREVENTION OF POST-OPERATIVE SORE THROAT - Naqvi, Nadeem; Mallhi, Arif Iftikhar; Asgher, Ali; Rafique, Umer (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the Comparison of the effect of intra-cuff ketamine versus alkalinized lidocaine for prevention of post-operative sore throat at a tertiary care hospital at Karachi.Study Design: Prospective comparative study.Place and Duration of Study: Liaquat National Hospital & Medical College, Karachi, from Apr to Jul 2018.Methodology: After taking informed written consent, severity of post operative sore throat pain, cough, hoarseness, laryngeal spasm & changes in heart rate & blood pressure was assessed and compared among patients undergoing General anesthesia with end tracheal intubation.Results: A total of 70 participants who were going under general anesthesia with endotracheal intubation as per inclusion criteria were included. Patients were divided into two groups, group K (intra-cuff ketamine) and group LA (alkalinized lidocaine). Severity of sore throat pain, cough, hoarseness, laryngeal spasm, and changes in heart rate & blood pressure were noted less commonly in ketamine group as compare to group Lidocaine Alkalinized (p>0.05).Conclusion: Intra-cuff alkalinized lidocaine significantly attenuated the severity of post, cough, hoarseness & laryngeal spasm especially in the early post-operative period, as compare to intra-cuff ketamine.